The minimal angle condition for quadrilateral finite elements of arbitrary degree - Acosta Rodriguez, Gabriel (2017)
We study W1,p Lagrange interpolation error estimates for general quadrilateral Qk finite elements with k≥2. For the most standard case of p=2 it turns out that the constant C involved in the error estimate can be bounded in terms of the minimal interior angle of the quadrilateral. Moreover, the same holds for any p in the range 1≤p<3. On the other hand, for 3≤p we show that C also depends on the maximal interior angle. We provide some counterexamples showing that our results are sharp.